The Influence of School Climate on Student Engagement Moderated by Peer Support in Students of MTs Islamiyah Guppi - Fuad Hasan Daulay; Siti Aisyah; Salamiah Sari Dewi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the effect of school climate on student engagement with peer support as a moderator variable in students of MTs Islamiyah Guppi. The background of this study is based on the importance of a positive school environment and peer support in increasing student engagement in learning activities. The research subjects were 269 students in grades VII, VIII, and IX with an age range of 13–15 years. This study used a quantitative approach with the Partial Least Square (PLS) analysis method. The research instruments included scales of school climate, peer support, and student engagement that had been tested for validity and reliability. Based on the results of the hypothesis test, it was found that school climate had a positive and significant effect on student engagement with a coefficient value of 0.475 and a p-value of 0.000. In addition, peer support also had a positive and significant effect on student engagement with a coefficient value of 0.475 and a p-value of 0.000. The results of the moderation test showed that peer support significantly moderated the relationship between school climate and student engagement, with a coefficient value of 0.131 and a p-value of 0.024. The total effect value of 0.606 indicates that the more positive the school climate and the stronger the peer support, the higher the level of student engagement in learning activities. This finding confirms that student engagement in school is influenced not only by a conducive school climate but also by social support among students, which strengthens these positive relationships.